2020
DOI: 10.1101/2020.09.14.295931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Syringeal vocal folds do not have a voice in zebra finch vocal development

Abstract: Vocal behaviour can be dramatically changed by both neural circuit development and postnatal maturation of the body. During song learning in songbirds, both the song system and syringeal muscles are functionally changing, but it is unknown if maturation of sound generators within the syrinx contributes to vocal development. Here we densely sample the respiratory pressure control space of the zebra finch syrinx in vitro. We show that the syrinx produces sound very efficiently and that key acoustic parameters, m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…When measured in vivo, ME captures both (i) the transformation of aerodynamical power into acoustic flow within the vocal tract, (ii) transmission efficiency through the airways, and (iii) the transformation of sound from the surface (mouth/beak/air sacs) to the environment (Titze and Palaparthi, 2018). ME varies greatly with bronchial pressure (Herbst, 2014), frequency (Zhang et al, 2019), vocal fold position, geometry and pathologies and also in between species (e.g., Brackenbury, 1979;Titze et al, 2010;Herbst, 2014;Maxwell et al, 2021) and values are reported between 10 −4 to 2% (e.g., a factor of −60 to −20 dB).…”
Section: Physiological Limitations To the Production Of Loud Soundsmentioning
confidence: 99%
“…When measured in vivo, ME captures both (i) the transformation of aerodynamical power into acoustic flow within the vocal tract, (ii) transmission efficiency through the airways, and (iii) the transformation of sound from the surface (mouth/beak/air sacs) to the environment (Titze and Palaparthi, 2018). ME varies greatly with bronchial pressure (Herbst, 2014), frequency (Zhang et al, 2019), vocal fold position, geometry and pathologies and also in between species (e.g., Brackenbury, 1979;Titze et al, 2010;Herbst, 2014;Maxwell et al, 2021) and values are reported between 10 −4 to 2% (e.g., a factor of −60 to −20 dB).…”
Section: Physiological Limitations To the Production Of Loud Soundsmentioning
confidence: 99%